FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PENDAMPINGAN SUAMI DALAM PROSES PERSALINAN - Novria Hesti; Zulfita Zulfita (Universitas Pahlawan, 2021)
The Mother's Care Movement (GSI) is a joint movement between the government and the community to improve the quality of life for women with the main objective of reducing the Maternal Mortality Rate (MMR) and Infant Mortality Rate (IMR) in order to improve the quality of Human Resources (HR). Maternal Care (ASI) is born in the context of reducing maternal mortality during childbirth, where one of the important elements in it is providing emotional support by presenting the husband in the delivery process. With the birth attendant, it is hoped that during the labor process a mother will feel confident and not afraid to face the labor process, this refers to the needs of the mother during labor, including the presence of a companion to go through the labor process. Research Objectives To find out the factors related to accompanying husbands in the delivery process.This type of research is analytic with a cross sectional study design which aims to determine the factors associated with accompanying husbands in the delivery process. This research will be conducted in Anduring Village in August-December. Sampling was carried out using a non-probability sampling technique, namely Quota Sampling, where the number of samples was determined based on a quota. The sample of this research is husbands who have wives who are pregnant in trimester II - III in Anduring Village. Data were collected using a questionnaire and analyzed quantitatively. More than half of the respondents had good husband's assistance, high level of knowledge, positive attitude, casual work, high education level in the process of wife's delivery. There is a significant relationship between the level of knowledge and attitudes in the wife's labor. There is no significant relationship between work and education level in the process of giving birth to a wife. It is hoped that health workers, especially midwives, to prepare husbands to face the wife's labor, this can be done and prepared when the wife is at the antenatal visit and improves programs on counseling or providing information and counseling about knowledge, attitudes and actions to the husband who acts as a companion in the delivery process. .